1977
DOI: 10.1152/ajpregu.1977.233.3.r83
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for enhanced uptake of ATP by liver and kidney in hemorrhagic shock

Abstract: It has been shown that infusion of ATP-MgCl2 proved beneficial in the treatment of shock; however, it is not known whether this effect is due to improvement in the microcirculation or direct provision of energy or a combination of the above or other effects. To elucidate the mechanism of the salutary effect of ATP-MgCl2, we have now examined the in vitro uptake of ATP by liver and kidney of animals in shock. Rats were bled to a mean arterial pressure of 40 Torr and so maintained for 2 hrs. After the rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All the chemical ingre dients necessary for FR generation, in fact, are available. During the ischemic stage, there is an increase in renal concentrations of catabolites derived from the anoxic degradation of adenine nucleotides, adenosine, inosine and hypoxanthine [37,55,56], The kidney contains xan thine dehydrogenase [57], which is converted to xanthine oxidase within 30 min of ischemia [36]. Peroxidation of the membrane lipids, furthermore, occurs during reper fusion only, since the production of malonyldialdehyde (the main product of such peroxidation) is not increased at the end of ischemia, but only after reperfusion [38].…”
Section: Hypothesis: the Case For Oxygen Free Radicals In Ischeinic-pmentioning
confidence: 99%
“…All the chemical ingre dients necessary for FR generation, in fact, are available. During the ischemic stage, there is an increase in renal concentrations of catabolites derived from the anoxic degradation of adenine nucleotides, adenosine, inosine and hypoxanthine [37,55,56], The kidney contains xan thine dehydrogenase [57], which is converted to xanthine oxidase within 30 min of ischemia [36]. Peroxidation of the membrane lipids, furthermore, occurs during reper fusion only, since the production of malonyldialdehyde (the main product of such peroxidation) is not increased at the end of ischemia, but only after reperfusion [38].…”
Section: Hypothesis: the Case For Oxygen Free Radicals In Ischeinic-pmentioning
confidence: 99%
“…Since oxygen content difference between arterial and mixed venous blood remained unchanged, ATP might contribute in part to the body's energy resources. Chaudry et al (1974Chaudry et al ( , 1977 stated that ATP administered exogenously entered into the cells and its beneficial effect appeared but not only through vasodilatation because more potent vasodilatory agents, such as ADP or AMP, failed to produce any beneficial effect.…”
Section: Oxygen Consumptionmentioning
confidence: 99%
“…Chaudry et al (1974Chaudry et al ( , 1977 have used ATP as an energy source for the treatment of shock. Sodium nitroprusside (SNP) has been widely used not only to produce controlled hypotension but also in the treatment of congestive heart failure (Miller et al 1976) and hypertensive crisis (Page et al 1955).…”
mentioning
confidence: 99%
“…When the concentration of ATP-MgCl, in the medium was increased to 2.5 mM, intracellular ATP levels in 'shock' muscles increased and showed approximately the same values as observed in control musclcs. It has becn shown that ATP can cross cell membranes of muscle (Chaudry and Gould 1970a), liver, and kidney (Chaudry et al 1975d). Thus, the reversal of insulin resistance could be due to the restoration of muscle ATP levels by external ATP (Chaudry et al.…”
Section: A4uscle a Tp Contentsmentioning
confidence: 99%